Ritual’s collective effervescence, awe, and social identity: psychosocial effects of the Pasto carnival - Rincón-Unigarro, Camilo; da Costa-Dutra, Silvia; Cisneros-Rodríguez, María-José; Díaz-Fuentes, Laura; Giraldo-Castillo, Natalia; Murcia-Infante, Angélica; Páez, Darío; Vargas-López, Mariana; Vásquez-Velásquez, Santiago (Frontiers in Psychology, 2025)
IntroductionThis study analyzes the experience of participating in the 2023 Carnaval de Negros y Blancos, a festive event that emphasizes southwestern Colombia’s African, Andean, and European traditions.MethodsWe surveyed a total of 163 participants, including dancers (n = 73, 44.79%), players (n = 47, 28.83%), and other artists (n = 43, 26.33%). Questions were asked about participation (type of role, number of days at the festival) and the quality of the experience according to the neo-Durkheimian model of collective gatherings (situated social identity, perceived shared attention and behavioral synchrony, fusion of personal and collective identity, perceived emotional synchrony, positive personal emotions, self-transcendent emotions, including awe, and experience of self-transcendence). The outcome variables were parochial altruism, identification with the community, the national, and humanity.ResultsThe participation experience was associated with all outcomes. The data supports that quality of participation in the event or collective effervescence, controlling for sociodemographic variables and intensity of participation, was associated to communal and national identification, but also to superordinate identification with all of humanity. Awe felt during Carnaval de Negros y Blancos correlates with the quality of experience, with social identification, and with superordinate identification with all of humanity. Mediation analyses show that collective effervescence influences community identity and parochial altruism through awe, but does not influence national or all of humanity’s identity.DiscussionWe discuss why a local multicultural event partially reinforces superordinate identities, the limitations of the study, and our research approaches.